Pharmacokinetics and pharmacodynamics of cannabigerol (CBG) in the C57BL/6Crl mouse - Zagzoog, Ayat; Halter, Kenzie; Ha, Nini; Jones, Alayna M.; Andres, Rachel; Kim, Andy; Michel, Deborah; Alcorn, Jane; Laprairie, Robert B. (Frontiers in Pharmacology, 2025)
IntroductionCannabis holds therapeutic potential; however, activation of the type 1 cannabinoid receptor (CB1R) via Δ9-tetrahydrocannabinol (THC) is also responsible for the characteristic “high” induced by cannabis. The pharmacology of the less abundant phytocannabinoid, cannabigerol (CBG), is poorly established, though it has been shown to exhibit promising therapeutic properties such as potential anxiolytic effects.MethodsWe assessed the pharmacokinetics (PK) and pharmacodynamics (PD) of CBG in C57BL/6Crl mice, hypothesizing that CBG would produce fewer PD effects than we had previously observed with THC, even when accounting for PK differences. Following oral (p.o.), intraperitoneal (i.p.), and intravenous (i.v.) administration, the PK profile of CBG was assessed via blood sampling at specified time points (10 min, 30 min, 1 h, 3 h, 6 h, 12 h, 18 h, and 24 h). The blood concentrations of CBG were quantified by High-Performance Liquid Chromatography-Tandem Mass Spectrometry (HPLC-MS/MS). A separate cohort of mice was treated with CBG and tested for cataleptic, hypothermic, anti-nociceptive, and locomotor effects to correlate the PK profile of CBG with CBG’s observed PD effects.Results and DiscussionOur data reveal that CBG was not intoxicating, even when accounting for the route of administration and blood concentration. Our findings support previous reports that CBG is not intoxicating and reveal that even if CBG were present at sufficiently high concentrations in cannabis products, it would not produce intoxicating effects like those of THC.